Neonatal Exposure to Citalopram Increases Pyramidal and Granular Cell Density in Dorsal Hippocampus of Male but not Female Adult Rats: A Quantitative Nissl Study - Kalbouneh,Heba M (Sociedad Chilena de Anatomía, 2019)
SUMMARY: Antidepressants use during pregnancy was associated with an increased risk of autism spectrum disorders. Animal models based on early life alterations in serotonin availability replicate some of the anatomical and behavioral abnormalities observed in autistic individuals. In recent years there has been a growing interest in the possible role of the hippocampus in autism. The aim of study is to examine the effects of neonatal antidepressant (CTM) exposure during a sensitive period of brain development on pyramidal and granule cells density of hippocampal formation. We examined the pyramidal and granular cells density of dorsal hippocampus using Nissl stained sections obtained from neonatal citalopram (CTM) exposed rats (5 mg/kg, twice daily, s.c.), from postnatal day 8 to 21 (PN8-21), saline and non-exposed rats. The density of pyramidal cells was significantly increased by 10.2 % in CA1, 10.6 % in CA3 and 13.2 % in CA4 in CTM treated compared with non-treated or saline treated animals (p<0.0001). The density of granule cells in the dentate gyrus was significantly increased by 12.0 % in CTM treated compared with non-treated or saline treated animals (p<0.0001). These findings were obtained only from male rats, suggesting a sexual dimorphism in neural development after SSRI exposure. These data suggest that the neonatal exposure to CTM may induce long-lasting changes in the hippcampal formation in adults, and such effects appear to preferentially target males.